Edukasi tentang Cara Memerah ASI yang Tepat dan Kompres Hangat sebagai Penatalaksanaan Bendungan ASI - Ayu Devita Citra Dewi; Bella Riska Ayu (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Breastfeeding problems are mostly caused by breast milk not coming out smoothly, which triggers accumulation of breast milk or breast milk dams. This can cause failure to provide exclusive breastfeeding. Nationally, the number of exclusive breastfeeding coverage in 2021 was 69.7%, but in 2022 it decreased to 67.96%. The aim of the activity is to increase breastfeeding mothers' knowledge about how to express breast milk and warm compresses as measures to manage breast milk dams. Method: counseling using a question and answer lecture method and educational videos containing steps for expressing breast milk and warm compresses on the breasts. Knowledge assessment is by interview (questionnaire). Results: The average pretest score was 65.9 and the average posttest score was 78.8. These results indicate an increase in knowledge of breastfeeding mothers after being given education using lecture methods and educational videos on how to express breast milk and warm compresses. It is hoped that all relevant parties will improve the exclusive breastfeeding program by educating the public about managing problems related to the breastfeeding process.